AN ONTOLOGY SEARCH FOR VIETNAMESE ACADEMIC DOCUMENTS IN COMPUTER SCIENCE - Nguyễn Hữu Vĩnh (Tạp chí Khoa học Đại học Đà Lạt)
Existing search engines were primarily designed to enhance keywork search, which provides little support for semantic meanings of a keyword query. This paper presents a semantic search tool based on ontological meanings for complete and effective searches. It proposes a conceptual model, database schema, and an instantiation of the tool. The proposed artefacts were evaluated using Vietnamese documents in three areas: Software engineering; Programming; and Computer networking. The evaluation results were presented and discussed.